DEVELOPMENT AND EVALUATION OF BIOADHESIVE MUCOSAL DOSAGE FORMS OF PILOCARPINE HCL FOR XEROSTOMIA THERAPY - Özlem Akbal Dağıstan; Nur Sena Başarır; Sinem Yaprak Karavana; Ayça Yıldız Peköz (Sabiad)
Objective: Saliva maintains vital mouth functions and acts as a barrier to dental health. Xerostomia, which is characterised as a feeling of dry mouth, adversely affects the patient’s quality of life. Palliative therapies, such as sialagogues, form the based on treatment of xerostomia. The FDAapproved sialagogue pilocarpine is currently recommended as the firstline medication for patients. Owing to its wide range of action, oral pilocarpine users may experience several negative side effects. The purpose of this study was to increase the duration of action and prevent systemic side effects of pilocarpine hydrochloride by designing and evaluating prolonged-release formulations of the drug using either xanthan gum, hydroxyethyl cellulose, or a combination of these two natural polymers buccal bioadhesive films. Material and Methods: The films were analysed for their physicochemical, mechanical, bioadhesive, swelling, in vitro release, and in vitro cytotoxicity. Results: Physicochemical and mechanical feature examinations revealed that the Xanthan-HEC combinations showed better results compared to the single polymer-used formulations. The in vitro dissolving profiles of all the optimal formulations showed a sustained release pattern with a steady-state plateau after an initial fast release. Using various release kinetic models to assess drug release kinetics revealed that the Higuchi and Korsmeyer-Peppas correlations are primarily followed by drug release from buccal films. Conclusion: The findings show that the mucoadhesive buccal formulation is a viable method for pilocarpine localised distribution that is both safe and effective in treating xerostomia. Further in vivo studies are planned to assess the pharmacokinetic and histopathological effects of the formulation.